Single channel abdominal ECG algorithm for real-time maternal and fetal heart rate monitoring - Ortega R., Arias; Gaitán González, M. J. (Revista Mexicana de Ingenieria Biomedica, 2018)
From a single channel abdominal ECG, a maternal (MHR) and fetal heart rate (FHR) detection method is proposed. This method is based on sequential processing: detection and cancellation of maternal QRS complexes, followed by fetal QRS complexes detection, involving hardware suitable processing techniques. The algorithm was tested on a group of 25 different gestational age pregnant women signals; its performance was assessed using detections obtained by another single channel method and an expert physician. Concordance was evaluated by Cohen’s kappa coefficient and sensitivity comparison was done by repeated measures ANOVA for method and gestational age (p < 0.05). Sensitivity behavior against fetal SNR was obtained as well as temporal coincidence of fetal and maternal complexes. Both methods presented similar high Cohen’s kappa coefficients, with detection success rates superior to 97% and 88% for maternal and fetal complexes respectively, but for 38 weeks of pregnancy the proposed method had lower maternal success rate than reference one (90%, p > 0.05). Proposed algorithm may be implemented in an independent platform and only requires operator supervision at the beginning of the process.